FREQUENCY OF MALNUTRITION IN PATIENTS WITH INTRAORAL CARCINOMA - stojanovic, milos (Acta medicae Medianae, 2024)
Malnutrition, or insufficient or poor nutrition, represents a lack of basic nutrients in a human organism. Being incapable of sufficient intake of nutrients, patients with intraoral carcinomas (ICs) are often affected by malnutrition. One of the most frequently used measures of nutritional status is the body mass index (BMI), an anthropometric parameter. When biochemical parameters are concerned, the level of serum albumin (SA) is the one most commonly employed. The aim of this study was to analyze the nutritional status of patients with IC by measuring the pre-post-treatment values of BMI and SA and to establish the prevalence of malnutrition in these patients. In the period from 2015 to 2016, we analyzed the patients with the diagnosis of IC treated at the Department of Maxillofacial Surgery, Clinic of Dental Medicine in Niš. The study sample included 20 patients. The results of our study support the notion that malnutrition in IC patients should be taken into consideration as one of the key factors of treatment success and complete rehabilitation of IC patients. A multidisciplinary approach and use of nutritional support therapy to correct malnutrition have to become an integral part of everyday practice of all clinics dealing with this pathology.